The Validity of Politicians as Marriage Witnesses from the Perspective of Islamic Law - Syahnur Aida Alifia; Sal Sabila Alamsyah; Muhammad Misbakul Munir (Al-Mahkamah: Islamic Law Journal, 2024)
. This research aims to investigate the validity of politicians as witnesses in marriage contracts from the perspective of Islamic law. The objectives of this study are to analyze the views of scholars regarding the requirements that must be fulfilled by marriage witnesses in Islam and to evaluate the suitability of politicians in that role. The research method employed is literature analysis, involving the exploration and analysis of various scholars' views on marriage witnesses in Islam found in classical Islamic legal texts as well as the opinions of contemporary scholars. The findings indicate that the majority of scholars emphasize that marriage witnesses must be a Muslim who is just, with additional emphasis on criteria such as maturity, integrity, and fairness. However, there are differing opinions regarding the validity of female witnesses. Additionally, the evaluation of the suitability of politicians as marriage witnesses according to Islamic law encompasses aspects such as moral integrity, honesty, and their leadership competence. This research provides relevant insights into understanding the role of politicians in the context of marriage in Islamic law and highlights the complexity in determining the suitability of witnesses in the institution of marriage within Islamic society.